Review of Help line Counseling 1323: Gambling Case Study - เดชปัญญาวัฒน์ สิริจันทร์; คุ้มศิริ ภาสกร; สุนันทชัยกุล ชญาภา; บุญมี ศิริกุล; หนูหล่ำ ชลันดา (Journal of Preventive Medicine Association of Thailand, 2019)
The objective of this research is to review behaviors, effect and process of help line counseling 1323, based on gambling case study. The methodology of this research is Survey research and selecting data from the record of participants who called counseling help line 1323 since 1st April to 31st December 2014. Number of line were 589 which related to gambling problems and 493 were samples. This research was analyzed by using basic data such as frequency, percentage, and Chi-square test. The result has showed that most of the samples who called counseling help line were male (65.1%) female (32%) at the age from 13-60 and above. Most of the cases called the help line by themselves, but some cases, Their spouse and/or parents called the help line. The type of gambling which was found the most is football betting, online gambling and cards. The causes of gambling addiction are the financial problem, influence by the other gamblers, and unemployment. The effect from gambling addiction is debt, family problem, and stress. In addition, the findings showed that sex, status and region related to types of gambling such as sport betting, card, and lottery. Moreover, the result revealed that the status family and stress problem were related at .05 statistical significance level. In summary: The research found that most of the samples of this research are male aged 21-40 with married status. Most of them live in Bangkok. Sex, status and region also correlated with the cause of gambling. The research found that financial problem is the major cause that leads to the gambling.